2021
DOI: 10.1371/journal.pntd.0009589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and outcome measurement tools reported in randomised controlled trials of treatment for snakebite envenoming: A systematic review

Abstract: Background Snakebite is a priority neglected tropical disease and causes a range of complications that vary depending on the snake species. Randomised clinical trials have used varied outcome measures that do not allow results to be compared or combined. In accordance with the Core Outcomes Measurements in Effectiveness Trials (COMET) initiative, this systematic review aims to support the development of a globally relevant core outcome set for snakebite. Methods All randomised controlled trials, secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Although the frequency of severe allergic reactions was low, there was one case that died as a direct result of antivenom induced anaphylaxis. Despite local envenoming being the most frequent indication for administering antivenom in much of Africa, its effectiveness for this indication is unproven, particularly if it is given late, and clinical trials are urgently needed [19]. Novel oral small molecule therapeutics may hold promise, particularly if they can be administered in rural clinics and thus reduce the time to treatment [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of severe allergic reactions was low, there was one case that died as a direct result of antivenom induced anaphylaxis. Despite local envenoming being the most frequent indication for administering antivenom in much of Africa, its effectiveness for this indication is unproven, particularly if it is given late, and clinical trials are urgently needed [19]. Novel oral small molecule therapeutics may hold promise, particularly if they can be administered in rural clinics and thus reduce the time to treatment [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…When good quality antivenom directed against the relevant biting species is available, it has been shown to effectively reverse the consumption coagulopathy induced by SVMPs. However, few clinical trials of antivenom in sub-Saharan Africa have been conducted, and none have compared antivenom to placebo [6][7][8][9][10] . In Nigeria, ''EchiTAb Plus-ICP'' (ET-Plus) equine antivenom restored the 20-minute whole-blood clotting time (20WBCT) in 83% of trial participants 6 .…”
Section: Limitations Of Antivenommentioning
confidence: 99%
“…If the cost of snakebite treatment was lower, it would not likely be argued that it is being overused. 1,3,6 To that end, it is essential to devise systematic and comparable methods for evaluating and reporting snakebite envenoming such that local, regional, and international data sets can be interpreted to their highest and best purpose to inform clinical decision-making.…”
Section: Acute Kidney Injury As a Complication Of Venomous Snakebite ...mentioning
confidence: 99%
“…5 In their recent review of snakebite envenoming, Abouyannis et al identified 14 published clinical trials in which acute kidney injury was one of the outcomes. 6 The findings of Bowden et al suggest the need for attention to acute kidney injury in clinical trials of snakebite envenoming, and, more specifically, suggest the possibility of modernizing the SSS to include acute kidney injury in order to optimize its utility in international trials testing traditional and novel snakebite envenoming therapeutics.…”
mentioning
confidence: 99%